110k views
5 votes
Drag the tiles to the correct boxes to complete the pairs. Not all tiles will be used.

Using the properties of integer exponents, match each expression with its equivalent expression.

Drag the tiles to the correct boxes to complete the pairs. Not all tiles will be used-example-1
User ScottJ
by
5.3k points

2 Answers

1 vote

Answer:

5-3 -----> 1/125

-5-3 ------> -1/125

(-5-3)-1 -------> -125

(-5-3)0 --------> 1

Explanation:

The other person is correct but i simplified it a little bit.

User SerialEnabler
by
4.3k points
2 votes

Answer:

(a)


5^(-3)=(1)/(125)

(b)


-5^(-3)=-(1)/(125)

(c)


(-5^(-3))^(-1)=-125

(d)


(-5^(-3))^(0)=1

Explanation:

(a)


5^(-3)

we can use property of exponent


a^(-n)=(1)/(a^n)

we get


5^(-3)=(1)/(5^3)


5^(-3)=(1)/(5* 5* 5)


5^(-3)=(1)/(125)........Answer

(b)


-5^(-3)

we can use property of exponent


a^(-n)=(1)/(a^n)

we get


-5^(-3)=-(1)/(5^3)


-5^(-3)=-(1)/(5* 5* 5)


-5^(-3)=-(1)/(125)........Answer

(c)


(-5^(-3))^(-1)

we can use property of exponent


(a^(n))^m=a^(m* n)

we get


(-5^(-3))^(-1)=(-5)^(-3* -1)


(-5^(-3))^(-1)=(-5)^3


(-5^(-3))^(-1)=(-5)* (-5)* (-5)


(-5^(-3))^(-1)=-125........Answer

(d)


(-5^(-3))^(0)

we can use property of exponent


(a^(n))^m=a^(m* n)

we get


(-5^(-3))^(0)=(-5)^(-3* 0)


(-5^(-3))^(-1)=(-5)^0

we can use property


a^0=1


(-5^(-3))^(0)=1........Answer

User Paul English
by
4.8k points